Primer registro de Russula pectinatoides Peck (Basidiomycota, Russulaceae) para Chile First record of Russula pectinatoides Peck (Basidiomycota, Russulaceae) from Chile - GÖTZ PALFNER (Universidad de Concepción, 2011)
Russulapectinatoides (Basidiomycota, Russulaceae), considered a holarctic species, is reported for the first time from Chile. It adds to the list of adventitious Russula and Lactarius species which form mycorrhizal associations with introduced ornamental and forest trees. A detailed description and an updated key for allochtonous agaricoid Russulaceae in Chile are provided.